Using the Mitrofanoff principle with technical of double Monti as a continent derivation in obese patient (2016)
Introduction: The Mitrofanoff principle was described in 1980 and is based on the derivation of the urinary tract by creating a conduit with a continent valve mechanism for catheterization. This procedure along with the intermittent clean catheterization described by Lapides changed dramatically the morbidity in patients with neurogenic pathology of the urinary tract. Moreover, obesity rates have increased exponentially in the last decades causing major difficulties during surgery for these patients. We present the case of a patient with neurogenic bladder and morbid obesity who underwent reconstruction of the urinary tract with a continent ileovesicostomy using the double Monti procedure. Objectives: We report the utility of the continent ileovesicostomy with double monti technique in patient whit morbid obesity at our center. Material and methods: We reviewed the literature published from January 1998 to January 2014 using the terms 'Monti ileovesicostomy', 'Yang-Monti', 'Catheterizable stoma', 'Obesity' in the Pubmed Database. We review the clinical history of the patient in whom we decided to perform this technique. Results: We describe the case of a 37 year-old patient with morbid obesity (BMI: 30) victim of a gunshot wound with spinal cord trauma in T1 causing secondary paraplegia, who underwent ileovesicostomy continent urinary diversion with double Monti technique. Conclusions: Creating catheterizables stomas with a double Monti technique is an effective technique in patients with morbid obesity with good results as this case demonstrates. © 2015 Sociedad Colombiana de Urología.